Sintetizador de audio analógico para prácticas STEM en el aula de clase (2017)
In this graduation project was designed a pedagogical practice that made use of a modular and low-cost audio synthesizer to innovate in teaching fundamentals of engineering and music. Students used vision, touch and hearing during practice, thus achieving multimodal learning (visual, kinesthetic and auditory). In this report you can find the entire design process of the pedagogical practice and the audio synthesizer that was implemented. The results are shown, which consists of the technical parameters of the synthesizer and an approach to the acceptance of the practice by a group of two students. Future work proposes an implementation in several groups of students that allows an evaluation of the impact on learning with statistical significance.